Testing the Effects of 3D Multiple Object Tracking Training on Near, Mid and Far Transfer - Harris, David J.; Wilson, Mark R.; Smith, Sarah J. R.; Meder, Natalie; Vine, Samuel J. (Frontiers in Psychology, 2020)
Cognitive training aims to develop domain general mental abilities to support functions like decision making, multitasking and performance under pressure. Research to date has indicated that cognitive training likely aids performance on lab-based cognitive tests, but there has been little demonstration of transfer to tasks representative of real-world high performance environments. This study aimed to assess transfer from a cognitive training intervention to near and mid-level transfer tasks, plus a far transfer test representative of real-world multitasking in a military environment. 84 participants were randomised to four independent training groups, using NeuroTracker, a cognitive training task based on 3D object tracking. There was no evidence for near transfer (to another object tracking task) or for far transfer to a route monitoring task designed to replicate real-world multitasking. There may, however, have been some improvement in working memory performance as a result of training. These findings raise further questions about whether domain general cognitive training will transfer to real-world performance. Effective uses of cognitive training may require more task specific training targeting mid-level transfer effects.